The Status of Opinions-Prevalence in the Juristic Methodology of Ayatollah Boroujerdi - Mansour Mahdavi (پژوهش‌های فقهی مسائل مستحدثه)
Received: 2023 May 2  |   Recieved in revised form: 2023 Jul 18   |   Accepted: 2023 Sep 9   |   Published: 2023 Oct 23In Islamic juristic methodology (Ijtihād), opinions-prevalence (Shuhrah) serves multiple functions and therefore, evaluating such prevalence is of great importance. There are various aspects to the ijtihād of Ayatollah Boroujerdi including shuhrah. This article aims to outline the components and steps of ijtihād according to Ayatollah Boroujerdi's perspective, based on his works, the recounts of his students, and related sources. Notably, some of these components have been formally incorporated into the ijtihād of Shitte jurists for the first time. Additionally, the significance of shuhrah will be explored within the ijtihād framework and in relation to consensus (Ijmā), and the sayings of the Prophet (Hadīths). It is worthy of note that shuhrah may be preferred over ijmā in certain exigencies and circumstances, according to Boroujerdi.Mahdavi, M. (2023) The Status of Opinions-Prevalence in the Juristic Methodology of Ayatollah Boroujerdi. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 214-235. Doi: https://doi.org/10.22091/RCJL.2023.8904.1012 .